Unequal contributions to CO₂ emissions along the income distribution within and between countries - Federica Cappelli (Fondazione Eni Enrico Mattei (FEEM), 2024)
The question of whether changes in income inequality affect CO2 emissions remains a topic of debate at both theoretical and empirical levels. The purpose of this paper is to examine the effect of changes in the full spectre of income distribution on consumptionbased CO2 emissions per capita. To do so, we estimate a dynamic difference-GMM model and a dynamic threshold regression model allowing for endogeneity on a panel database covering 107 countries between 1990 and 2019. Our analysis highlights how different income classes contribute very differently to consumption-based CO2 emissions. In addition, by accounting for between-country inequalities in the average income of each income group, we uncover non-linearities in the impact on carbon emissions. More specifically, the impact of an increase in the income share of the top 10% on per capita consumption-based carbon emissions varies according to their average income level: it is negative at lower income levels and becomes positive as their income rises. The contribution of the middle class is negative at all income levels, while the CO2 contribution of the poorest segments is negligible.
Keywords: D31; D63; Q54; Q57; 330; Inequality; Emissions; Income Distribution; Climate Change